Religious Character Education Model Based On Local Wisdom In The Era Of Disruption 4.0 At MTs Baiturrahmah Pamekasan - Fithriyah, Imaniyatul; Afandi, Afandi; Hasanah, Iswatun; Nofita R, Roro Kurnia (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2021)
This study aims to reveal findings about the exploration and internalization of religious character values ​​based on local wisdom at MTs Baiturrahman Pamekasan. This type of research is qualitative with a case study approach; data mining is done through observation, interviews, and FGDs as well as relevant documents. The research data are then analyzed by organizing, sorting, grouping, coding, and categorizing the data. The results showed that the exploration of religious character values ​​based on local wisdom consisted of three value clusters, spiritual, ukhuwah Islamiyah, and nationality which were then internalized through dluha prayer activities, reading short suras, exemplary, habituation, giving advice, discipline, scouting. sports, traveling tadarus, and learning strategies. The value exploration and internalization process were then constructed into a new model, namely; holistic spiritual model, integrative learning model and religious social model.